Tradability, productivity, and understanding international economic integration - Paul Bergin; Reuven Glick (University of California, Department of Economics, 2005)
This paper develops a two-country macro model with endogenous tradability to study features of international economic integration. Recent episodes of integration in Europe and North America suggest some surprising observations: while quantities of trade have increased significantly, especially along the extensive margin of goods previously not traded, price dispersion has not decreased and may even have increased. These observations challenge the usual understanding of integration in the literature. We propose a way of reconciling these price and quantity observations in a macroeconomic model where the decision of heterogeneous firms to trade internationally is endogenous. Trade is shaped both by the nature of heterogeneity
Keywords: F40; 330; trade costs versus productivity; Wirtschaftsintegration; Zwei-Länder-Modell; Offene Volkswirtschaft; Internationaler Preiszusammenhang; Außenwirtschaft; Internationale Marktsegmentierung; Theorie